The Influence of Operating Costs on Return on Assets at PT. Sinar Harapan in Jakarta - Waryanto, Hendro (PINISI Discretion Review, 2019)
Company management must be able to manage everything that can affect the entire process in the company. This study aims to determine the effect of operational costs on Return on Assets at PT. Sinar Harapan in Jakarta. The method used was explanatory research with a sample of 5 years of financial statements. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study variable operational costs obtained a minimum variance of 71.2 billion and a maximum variance of 89.8 billion with an average of 84.44 billion with a standard deviation of 75.11 billion. Return on Assets obtained a minimum variance of 0.7% and a maximum variance of 0.9% with a rating score of 8.04% with a standard deviation of 0.551%. Operating costs have a significant effect on Return on Assets with a regression equation Y = 17.517 + 0.0565X, and a correlation value of 0.885 or strong with a determination of 78.3%. Hypothesis testing obtained a significance of 0.046 <0.050.